4.3k views
4 votes
Solve the system of equations.
y = 6x + 13
y = 2x + 1

2 Answers

0 votes

Answer:

{y,x} = {-5,-3}

Explanation:

System of Linear Equations entered

y - 6x = 13

y - 2x = 1

Graphic Representation of the Equations

-6x + y = 13 -2x + y = 1 (attached)

Solve by Substitution

y = 2x + 1

(2x+1) - 6x = 13

- 4x = 12

4x = - 12

x = - 3

y = 2x+1

x = -3

y = 2(-3)+1 = -5 (final answer)

hope it helps you!

Solve the system of equations. y = 6x + 13 y = 2x + 1-example-1
User Mohamed Gamal
by
4.8k points
5 votes

Answer:

x=-3. y=-5

Explanation:

Equating both equations,

6x + 13 = 2x + 1

6x - 2x = 1 - 13

4x = -12

x = -3

Plug in the value of x in the given first equation,

y = 6* (-3) + 13 = -18 + 13 = -5

User Louis Yang
by
5.3k points